Rancang Bangun Lampu Taman Menggunakan Panel Surya Sebagai Sumber Energi Baru Dan Terbarukan ( Studi Kasus : Taman Kampus Fakultas Teknik Universitas Hamzanwadi ): Rancang Bangun Lampu Taman Menggunakan Panel Surya Sebagai Sumber Energi Baru Dan Terbarukan ( Studi Kasus : Taman Kampus Fakultas Teknik Universitas Hamzanwadi ) - Zaljalaliwal Ikrom, L. Abdi; muhammad iman, darmawan (Jurnal Teknologi Lingkungan, 2025)
Sunlight is a renewable energy. Sunlight can be converted into electrical energy and used to power garden lights at the Faculty of Engineering, Hamzanwadi University. The aim of this research is to design and build garden lights using solar panels at the Faculty of Engineering, Hamzanwadi University. This research is a type of experimental research with quantitative descriptive analysis. In this research, a wattmeter was used to calculate the current and voltage on the solar panel. The experiment was carried out for 7 consecutive days. Current and voltage measurements were carried out at peak solar hours at 10.00, 11.00, 12.00, 13.00, 14.00 and 15.00. The results of this research are the Prototype of Solar Garden Lights with an average power produced by solar panels of 15.5 Watts with the largest output power reaching 21.3 Watts and the smallest output power being 1.3 Watts. The average daily efficiency level produced by solar panels is 53.8% and the lowest efficiency is 39.9% and the highest efficiency is 57.5%. Low power efficiency at certain times can be influenced by several factors, such as weather conditions and the condition of the Solar Panel system and using a battery with a capacity of 12V/12 Ah which can power a 10 Watt LED AC light load stably for 11 hours.